Assessment of oat genotypes for resistance to frit fly in the conditions of the Kirov region - O. A. Zhuikova; G. A. Batalova (Аграрная наука Евро-Северо-Востока)
The oat fly (Oscinella frit L.) is a dangerous pest in oat crops. Studies on resistance to phytophagus were conducted in 2016-2021. The stability of 200 promising lines and varieties bred by the Federal Agricultural Research Center of the Nort-East named N. V. Rudnitsky was evaluated in the nursery of a competitive test under natural conditions for the development of the pest according to the scale of the All-Russian Research Institute for Plant Protection, the percentage of the stem damage by larvae was determined on the basis of "drying of the central leaf during the period "tillering-shooting" trait. The best conditions for the development of the pest were formed in 2016. (Ij = 3.0) and 2021 г. (Ij = 2.7), with maximum plant damage of 34 % in hulled and 22 % in naked genotypes, respectively. Unfavorable conditions for the phytophagus developed in 2017 (Ij = -2.7) and 2019. (Ij = -2.9) – damage to plants did not exceed 3 %. In 2018 and 2020, with the index of environmental conditions close to zero (Ij = -0.41 and 0.10, respectively), the damage of oat plants by the oat fly (Oscinella frit (L.) did not exceed 5 %. The studies established an inverse correlation between the damage of oats by the oat fly and the HTC during the "sowing-tillering" period (r = -0.73), total (r = -0.30...-0.39) and productive bushiness (r = -0.59...-0.77), grain yield (r = -0.20...-0.61). A direct correlation was established between plant damage and the plasticity of genotypes to damage (r = 0.88). Lines with minimal stem damage have been selected: 233h12, 394h12, 251h14, 194h13, 63h11, 21h12o, 153h13, 157h13, 65h11, 72h11. Low plasticity was noted in the lines: 178h13, 4h14, 114h12, 4h12, their yield did not change significantly from the amount of damage by oat fly (Oscinella frit (L.). The most stable according to the studied trait were the lines: 4h14, 178h13, 2h12o, 63h11, 4h12 and varieties Sapsan, Falenets.